Single-Cell Mechanical Characterization in Constriction-Based Cytometry - Abarca-Ortega, A (Elsevier Ltd, 2024)
Mechanical characterization of suspended cells by constriction-based microfluidic devices has currently various limitations related to the available analysis models. In this work, we propose a new methodology to analyze the experiments. This approach is based on numerical simulations to describe fluid forces and cell deformation and on an extension of the quasi-linear viscoelasticity theory developed by Fung. The cells are considered visco-hyperelastic, homogeneous, and isotropic. The approach allows for assessing the mechanical parameters of individual cells, which is not possible using previous approaches, notably increasing the power of the constriction-based microfluidic technique. A practical procedure to compute mechanical parameters is proposed and demonstrated by analyzing experiments with suspended cells. The methodology developed in this work provides a convenient tool to overcome critical limitations of the state of the art and to leverage the potential of these microfluidic devices. © 2024 The Authors